Outdoor propagation predictoin and measurements point to point for wireless LAN application - Ahmed, Naji Abdul Elgader (2008)
Wireless Local Area Networks (WLANs) have emerged as a powerful architecture capable of supporting the requirements of broadband wireless communications. In this project, an outdoor propagation prediction is made for a point-to point microwave link (bridging) at Kolej KRP Universiti Teknologi Malaysia (UTM), Johor, Malaysia. The link operates at frequency 5.8 GHz based on IEEE 802.11a standard, the antenna gains was 17 dBi for both transmitter and receiver. The transmitted power was 18 dBm. The measurement of the signal strength was carried out in the site where the link stands. The transmitter antenna mounted on the top of the fellow office ??, while the receiver distance 113m, at the building ??. A simulation of the same microwave link was carried out using a site specific propagation prediction tool provided by Site Ware Technologies. The simulation tool is a three-dimensional (3-D) ray tracing code employing modified shoot and bounce ray (SBR) method know as the Vertical Plane Launch (VPL). Then that presented simulation result into three dimensional using Matlab software. The result From VPL simulation is a path loss about -54 dB, the delay spread equal to 0.068 ns. The measured signal strength on the field was -64 dBm which is less than the predicted from the simulation by 28 dB. Due to many factors influencing the simulation like the data base accuracy, system errors the which they led the differences between the measured and predicted signal strength.